Challenges in parathyroid cancers: a review - Sujith Indeewara Wijerathne,; Rajeev Parameswaran, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Parathyroid carcinomas are rare neoplasms, with a reported incidence of less than 1% of cases of primary hyperparathyroidism. Diagnosis and treatment of parathyroid carcinoma remains a challenge, as many of the pathologic features are neither sensitive nor specific in differentiating from benign parathyroid lesions. The rule of 3’s (serum calcium of more than 3mmol/L and size of the adenoma being more than 3cm) is helpful in risk identifying a cancer. Ultrasound of the neck and Tc-99m pertechnetate/Tc-99m sestamibi (MIBI) scan remains the two main modalities of investigation of parathyroid disease. Although en-bloc treatment is recommended for parathyroid cancer, it is only performed in up to 12% of cases. This review illustrates the challenges in diagnosis and treatment of parathyroid carcinoma.